Motivation for and Possibilities of Increasing Table Beet Root Cultivation - Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2002)
Due to its manifold nutritional-physiological effects, table beet root would deserve more attention. Its active components and their role in human therapy and prevention should rank it higher in our list of vegetables.The actual some 100 ha area under beet root could be considerably increased, if its role in nutrition and its varied products were universally known.Most of the physiologically favourable effects are related to its pigment content. Pigment content can be increased by choosing proper varieties and applying cultural methods which, favourably influence red pigment synthesis (optimal sowing date).The high Mg-content and advantageous ion ratio must also be mentioned. They can be increased by Mg leaf fertilisation, as can solids content and foliage resistance.The special knowledge accumulated in literature ought to be made known to experts so as to help them to set up trials and to introduce results into practice.